ANALISIS PENGARUH RELIGIUSITAS, TINGKAT PENDAPATAN, KEPERCAYAAN, DAN KESADARAN DIRI TERHADAP MINAT MUZAKKI DALAM MEMBAYAR ZAKAT - Fikri AD, A Syihabul; Adityawarman, Adityawarman (Diponegoro Journal of Islamic Economics and Business, 2021)
This article aims to determine the effect of the independent variables, namely religiosity, income level, trust, and muzakki’s self-awareness on paying zakat as the dependent variable. Muzakki here are employees of the Regional Office of the Ministry of Religion of Central Java Province. Population in this study were employees of the Regional Office of the Ministry of Religion of Central Java Province. By using Slovin formula, 72 sample of respondents are generated. The data collection method used in this study was a questionnaire with a Likert scale. This study was analyzed using multiple regression assisted by using the SPSS application version 25. The results of the analysis show that religiosity, income level, and self-awareness have a positive and significant effect on the interest of muzakki (employees of the Regional Office of the Ministry of Religion of Central Java Province) in paying zakat partially and simultaneously while a trust does not affect. However, trust influences simultaneously. The R square value of 0.774 indicates that 77.4% interest in paying zakat can be explained by the independent variable and the remaining 22.6% is explained by other factors outside the research.